Transformasi Ruang Perkotaan di Permukiman Nelayan (Studi Kasus: Tambakmulyo, Semarang) - Bambang Setioko (TATALOKA, 2013)
Fisherman settlements are physically different to common urban settlements, because it has a uniqueness reflect to their tradition and culture. Some periodical observation has been made in Tambakmulyo fisherman settlement-Semarang shown different phenomena, which the fisherman’s urban space has visual similarity to the common open space. The settlement image has been melting away because of some unique activities has been less dominant conducted. This research has a purpose to get more understanding about the urban space transformation in both physical and socio-spatial point of views, while deductive-rationalistic approach also have been used to support research objectives. In addition, a descriptive-qualitative method has been proposed in order to reveal the urban space transformation phenomena. The urban space transformation in the fisherman settlements has been occurred, based on the physical form analysis and socio-spatial observation. Furthermore, this study has been successfully finding the urban space transformation phenomena, from the sea oriented toward the mainland, which is the fisherman unique activities are no longer dominated their urban space.